Cartografie immaginarie - Smail, Daniel Lord (Firenze University Press, 2025)
How, in the years before the advent of urban maps, did city residents conceptualize and navigate their communities? In his strikingly original book, Daniel Lord Smail develops a new method and a new vocabulary for understanding how urban men and women thought about their personal geography. His thorough research into property records of late medieval Marseille leads him to conclude that its inhabitants charted their city, its social structure, and their own identities within that structure through a set of cartographic grammars which powerfully shaped their lives. Imaginary Cartographies opens up powerful new means for exploring late medieval and Renaissance urban society while advancing understanding of the role of social perceptions in history. Through a rigorous method of analyzing notarial written sources, this book offers new interpretative categories for the history of medieval space, before the development of visual cartography.